Identifikasi Kandungan Mineral Magnetik Guano di Gua Solek dan Gua Rantai Menggunakan Metode Scanning Electron Microscope (SEM) - Wardina Nasution (PILLAR OF PHYSICS, 2013)
The guano’s Cave Solek and Cave Rantai has a large magnetic susceptibility values. The value of magnetic susceptibility shows large concentrations of magnetic minerals contained in the cave. Based on the magnetic susceptibility values can be specified types of magnetic minerals. Determination type of magnetic minerals have done before by using the method of rock magnetization IRM and XRD methods, however, to see the surface morphology and elemental composition of magnetic minerals have not been done. The research  to make identification surface morphology and composition of guano magnetic minerals in Cave Solek and Cave Rantai use Scanning Electron Microscope (SEM). The writer hope this research can confirm of true result in this measuring with other methods of rock magnetism. This research used SEM instrument combine with EDS type Philips CM 12 pw 6030. There are 7 samples used in this research devided by 4 samples from Solek Cave and 3 samples from Rantai Cave. Guano samples take based variation of the magnetic susceptibility that has been known previously. The observation of measuring about surface morphology of guano samples Cave Solek and Cave Rantai use SEM image magnification can not be analyzed because it that is too small. Therefore used by EDS analysis showed that the chemical elements forming magnetic minerals. The result of EDS identification show of magnetic mineral content Solek Cave and Cave Rantai dominated by a mineral that consists of the element iron (Fe) and oxygen (O) which is a magnetic mineral-forming elements of the group that is titanium magnetite of iron oxide (Fe3O4), hematite (Fe2O3) and ilmenite (FeTiO3), in addition it be found as well mineral nonmagnetic an element of such as the andalusite (Al2SiO5), siderite (FeCO3) and quartz (SiO2).   Keywords: Guano, Consentration of Magnetic Mineral, Surface Morphology, Elemental Composition of Magnetic Mineral SEM and EDS.